CARACTERIZAÇÃO DA FORRAGEM DE LINHAGENS DE MILHO DE GRÃOS DENTADOS E DUROS EM DUAS ÉPOCAS DE SEMEADURA - SPADA, CECILIA APARECIDA (2015)
In the search for new genotypes of maize for silage characterization of lineages key point is to develop new hybrids. The objective of this study was to evaluate and characterize maize lines with textures of hard grain and notched in two sowing dates. They were evaluated 8 lines from the breeding programs of the Universidade Estadual de Maringá (UEM) and the Universidade Estadual do Centro Oeste (UNICENTRO), including 4 flint texture and 4 dent texture, and two commercial hybrids with contrasting textures as witnesses. The treatments were evaluated in two sowing dates, October and December 2013, in Guarapuava-PR. The occurrence of foliar diseases was evaluated. The cut of silage in forage point was made when the grains reached 2/3 of milk line. The evaluated characteristics were yield of dry matter forage, dry matter forage and its components (stem, leaves, bracts+cob and grains), participation in dry matter of plant parts (stem, leaves, bracts+cob and grains), in situ digestibility of dry matter, neutral detergent fiber, acid detergent fiber, lignin, cellulose, hemicellulose and yield of digestible dry matter. There was a significant effect of genotypes x seasons, for most production traits, but the chemical variables showed no interaction effect. The genotypes of flint grains texture had higher foliar disease resistance. The hard texture genotypes had higher dry matter yield of forage compared to soft texture genotypes. The dry matter digestibility was not influenced by grain texture. The M01D and G02F lines stood out with greater production of digestible dry matter.